2017
DOI: 10.1021/acssuschemeng.6b02573
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide Ion as Oxidative Desulfurizing Agent for Aromatic Sulfur Compounds in Ionic Liquid Media

Abstract: The generation of superoxide (O2 •–) in ionic liquids (ILs) has been used to destroy hazardous materials. In this study, O2 •– was used for the oxidative desulfurization of benzothiophene (BT) and dibenzothiophene (DBT) in two ILs as reaction media. The O2 •– was released by dissolving potassium superoxide in 1-butyl-1-methylpyrrolidinium bis­(trifluoromethylsulfonyl)­imide [BMPyrr]­[TFSI] and n-methoxyethyl-n-methylmorpholinium bis­(trifluoromethylsulfonyl)­imide [MOEMMor]­[TFSI]. The highest conversion perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 78 publications
1
7
0
Order By: Relevance
“…Remarkably, it was found that O2 − destroyed close to 90% of the thiophene in [EDMPAmm][TFSI] at ambient conditions. This result was in good agreement with the findings of recent studies (Chan et al, 2008;Hayyan et al, 2015b;Hayyan et al, 2016b). Chan et al (2008) zation process.…”
Section: Destruction Of Thiophenesupporting
confidence: 93%
See 1 more Smart Citation
“…Remarkably, it was found that O2 − destroyed close to 90% of the thiophene in [EDMPAmm][TFSI] at ambient conditions. This result was in good agreement with the findings of recent studies (Chan et al, 2008;Hayyan et al, 2015b;Hayyan et al, 2016b). Chan et al (2008) zation process.…”
Section: Destruction Of Thiophenesupporting
confidence: 93%
“…Hence, they have been used to desulfurize fuels by various methods, including extraction (Ferreira et al, 2014;Lu et al, 2014) and oxidative desulfurization (Jiang et al, 2014;Lü et al, 2014). Recently, our group reported the possibility of using O2 − generated in ILs to destroy chlorinated hydrocarbons and sulfur compounds (Hayyan et al, 2012f;Hayyan et al, 2012e;Hayyan et al, 2015b;Hayyan et al, 2016b;AlNashef et al, 2013). Therefore, it also was worthwhile to explore using O2 − to destroy sulfur compounds in one of the studied ILs.…”
Section: Introductionmentioning
confidence: 99%
“…Many solid, liquid and gas oxidizers have been evaluated. Inorganic chemicals such as oxone [32] , sodium persulfate [33] , potassium superoxide [34] , potassium dichromate [35] , sodium percarbonate [36] , sodium perchlorate [37] , hydrogen peroxide [38] , sodium hypochlorite [39] , solid oxidizers such as cyclohexanone peroxide [40] and organic chemicals such as t-butylhydroperoxide [41] and cumene hydroperoxide [42] as liquid oxidizers are used. The most distinctive feature of cyclohexanone peroxide as solid organic oxidizers and cumene hydroperoxide and t-butylhydroperoxide as liquid organic oxidizers is that they can all dissolve in the organic phase or fuel, thereby directly oxidizing sulfur compounds [43] , [44] .…”
Section: Introductionmentioning
confidence: 99%
“…Some of the non-conventional ways to remove sulfur are currently being tested including biodesulfurization (BDS) [3][4][5], adsorptive desulfurization (ADS) [6][7][8], extractive desulfurization (EDS) [9][10][11][12], and oxidative desulfurization (ODS) [13,14]. Compared to BDS and ADS, EDS could be operated at mild conditions with the use of suitable extractant to desulfurize fuel oil.…”
Section: Introductionmentioning
confidence: 99%